2022
DOI: 10.3390/su14042241
|View full text |Cite
|
Sign up to set email alerts
|

Land Use, Landform, and Soil Management as Determinants of Soil Physicochemical Properties and Microbial Abundance of Lower Brahmaputra Valley, India

Abstract: Due to the shifting course of the Brahmaputra River, the fluvial landforms of the Brahmaputra Valley of Assam, India, are prone to changes in landform and land use. For sustainable soil management under such conditions, it is crucial to have information about soil physicochemical and biological properties for different land uses. Therefore, the present study was conducted to investigate the soil physicochemical properties and soil microbial population across five major land uses under different landforms, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Tellen & Yerima (2019) describe the chemical fertilizers and weedicides used for soil fertility maintenance in the area as typically containing some high amounts of cations, which could help to balance out the negative charges lost from the soil's exchange complex of cultivated soils as losses occur due to processes such as sheet erosion induced by high tillage and weeding frequencies and low organic matter in the control and the five cropping plots. The range in value of the property in the study area is not very wide, with the lowest being about 5.3 and the highest being about 6.9; however, the fact that the pH values of the cropping plots are significantly lower than those of the control is an indication of the fact that losses of cations have been occurring from the soils of the cultivated plots, which is very much in agreement with the findings of many research workers (Sadiq et al, 2021;Tumayro & Tesgaye, 2021;Haile et al, 2022;Hota et al, 2022). This suggests that where effective soil fertility amendments are introduced, declines in pH level cannot only be minimized but even be reversed.…”
Section: Soil Reaction (Ph)supporting
confidence: 90%
See 1 more Smart Citation
“…Tellen & Yerima (2019) describe the chemical fertilizers and weedicides used for soil fertility maintenance in the area as typically containing some high amounts of cations, which could help to balance out the negative charges lost from the soil's exchange complex of cultivated soils as losses occur due to processes such as sheet erosion induced by high tillage and weeding frequencies and low organic matter in the control and the five cropping plots. The range in value of the property in the study area is not very wide, with the lowest being about 5.3 and the highest being about 6.9; however, the fact that the pH values of the cropping plots are significantly lower than those of the control is an indication of the fact that losses of cations have been occurring from the soils of the cultivated plots, which is very much in agreement with the findings of many research workers (Sadiq et al, 2021;Tumayro & Tesgaye, 2021;Haile et al, 2022;Hota et al, 2022). This suggests that where effective soil fertility amendments are introduced, declines in pH level cannot only be minimized but even be reversed.…”
Section: Soil Reaction (Ph)supporting
confidence: 90%
“…In the literature, substantial research information is available on the effects of various CLUPs on SOC, TN, and pH, but the findings across different landscapes are still controversial. Many researchers (for example, Abbasi et al, 2007;Abad et al, 2014;Takele et al, 2014;Bore et al, 2015;Dengiz et al, 2015;Kalu et al, 2015;Chemada et al, 2017;Olorunfemi et al, 2018;Galindo et al, 2022;Paramesh et al, 2022;Shi et al, 2010;Wang et al, 2021;and Hota et al, 2022) observed that paddy rice had a higher SOC content than forested soil, while Jonczak (2013) found out that fallow land had a higher SOC content than forested soil. Pham et al (2018b), on the other hand, found that soils under planted acacia and rubber forest covers and arable land had higher SOC levels than those under natural forest, while Mengistu et al (2022) observed that the SOC values of soils under cropland and Eucalyptus camaldulensis planted fallows are not significantly different from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation to the increased extremities of hydrologic phenomena (droughts and floods) and the retention of water are indispensable in light of climate change [16]. Therefore, analyzing the suitability of soil textural types, fertility, topography and crop varieties may increase the profitability of the given land use type if managed site-specifically [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The construction of infrastructure such as roads and railways together with the associated urban development often results in landscape modifications and changes in human activities in the areas where they traverse [7][8][9][10]. The LULC changes lead to deforestation, water scarcity, loss of biodiversity [11,12] and water pollution [13]. While social development and poverty reduction are key objectives of many development corridors; Hope and Cox (2015) observed that less attention has been given to impacts on natural capital (e.g., water, forests, and other key biodiversity areas) which directly impact local livelihoods [14].…”
Section: Introductionmentioning
confidence: 99%